The role of social support on the relationships between internet use and sleep problems in adolescents during COVID-19 pandemic: a multicentre study - BORAN, PERRAN (My University, 2022)
Background: This study examines the frequency of problematic internet use and sleep problems in adolescents aged 14–18 years during the COVID-19 pandemic and identifies the impact of factors such as sociodemographic characteristics, internet habits, changes in daily life, and perceived social support on these problems. Methods: This multicentre study was a questionnaire-based online survey study. The questionnaire included the Young Internet Addiction Scale, the Pittsburgh Sleep Quality Index, and the Multidimensional Scale of Perceived Social Support, as well as questions about demographic information, internet habits, and changes in daily life during pandemic. Several multivariate Backward logistic regression models were run to determine the variables that predicted problematic internet use and poor sleep quality. Results: It was determined that the frequency of problematic internet use was 15.5%, and the frequency of poor sleep quality was 47.8%. Poor sleep quality was found 2.5 times higher in problematic internet users. The perceived social support was found insufficient in adolescents with problematic internet use and poor sleep quality. Various factors such as the excessive use of internet and social media, low school success, lack of physical activity, lack of rules for internet use at home, and worsening of relationships with parents were found to be predictive factors for these problems. Conclusions: Problematic internet use during the pandemic is associated with worsening sleep quality in adolescents. It is important to create special interventions for problematic internet use and sleep problems that develop in adolescents as a result of restrictions during the pandemic.
Keywords: COVID-19; adolescent; problematic internet use; sleep problems